A study of nuclear track counting and granulometry for monazite: A comparision of the sdc morphology toolbox and image processing toolbox / Naharudin Mustafa - Naharudin, Mustafa (2012)
The main aim of this work is to establish a technique to prepare the image of nuclear track detector in the form of thin film, LR 115 Type 2. This research also aims to develop the image processing scripts using SDC Morphology toolbox and Image Processing toolbox in conjunction with MATLAB as a programming platform. The scripts were applied to find the segmentation limit of over-lapping nuclear tracks, nuclear tracks counting and granulometry (area and diameter determination) in the images obtained. We finally compare the toolboxes capability in processing the image. The research found that the SDC Morphology toolbox is more precise than Image Processing toolbox when the exposed time of radiation to track detector is less than 30 hours. Then, the segmented over-lapping objects were obtained if the over-lapping area is less than the segmentation limit of over-lapping area. Keywords: Morphology Image Processing; MATLAB; SDC Morphology Toolbox